2004
DOI: 10.1182/blood-2003-08-2859
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells in infantile hemangioma

Abstract: Infantile hemangioma is an endothelial tumor that grows rapidly after birth but slowly regresses during early childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
118
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(131 citation statements)
references
References 16 publications
9
118
0
4
Order By: Relevance
“…The presence of EPCs in proliferating hemangiomas 8 and increased circulating EPC levels in hemangioma patients, 7 in combination with the appearance of endothelial-lined vascular channels in the involuting phase, support our hypothesis that HemECs arise from HemEPCs. We used the ES response to compare the HemEPCs to HemECs and normal cbEPCs.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The presence of EPCs in proliferating hemangiomas 8 and increased circulating EPC levels in hemangioma patients, 7 in combination with the appearance of endothelial-lined vascular channels in the involuting phase, support our hypothesis that HemECs arise from HemEPCs. We used the ES response to compare the HemEPCs to HemECs and normal cbEPCs.…”
Section: Discussionsupporting
confidence: 70%
“…4,6 We and others have identified endothelial progenitor cells (EPCs) in hemangioma tissue and circulating blood of patients with hemangiomas, respectively. 7,8 These findings suggest that a hemangioma may arise from the clonal expansion of an EPC.…”
Section: Introductionmentioning
confidence: 93%
“…2 Mast cells have been proposed to have a role in hemangioma progression 3 as have endothelial progenitor cells. 4 Hemangioma endothelial cells were shown to express the lymphatic endothelial marker LYVE-1, suggesting that these cells are arrested in an early vascular differentiation state. 5 The nonrandom distribution of facial hemangiomas has raised ideas relating to developmental patterning and the deposition of precursor cells.…”
mentioning
confidence: 99%
“…Early proliferating hemangiomas contain endothelial cells that express CD133 and CD34, markers for endothelial precursor cells, suggesting that the endothelial cells in proliferating hemangiomas may be arrested at an immature stage of vascular development. 10,11 Third, some aspects of hemangioma resemble that seen in the placenta. An unexpected set of tissue-specific markers co-expressed by both infantile hemangiomas at all stages of their evolution and placental vessels has suggested that the vasculature of the placenta and hemangioma may share a common cellular origin.…”
mentioning
confidence: 99%